Human immunodeficiency virus infection in women undergoing treatment for cervical neoplasia: Prevalence and the feasibility of routine screening - Chumnan Kietpeerakool (2018)
This study was undertaken to evaluate the prevalence of human immunodeficiency virus (HIV) infection and the feasibility of routine HIV screening in women undergoing various treatment of cervical neoplasia at Chiang Mai University Hospital between October 2004 and October 2006. Four hundred and ninety five women were recruited for HIV screening with the opt-out approach performed. In this study, thirty-seven (7.47%) women had a previous diagnosis of HIV infection with a mean duration 4.16 years (range: 1-15 years). The remaining 458 women consented to have an HIV test. Six women (1.31%) were newly identified as HIV seropositive, giving an overall prevalence of 8.69%. In conclusion, the prevalence of HIV infection in this study was considerably high and routine HIV screening is feasible because of the high acceptance rate.